Changes in voice quality, swallowing, and pulmonary function after parathyroidectomy for secondary hyperparathyroidism - Fong-Fu Chou; Jin-Bor Chen; Shun-Chen Huang; Yi-Chia Chan; Shun-Yu Chi; Chi-Chih Lai; Yi-Ju Wu; Huang-Chih Chang (Asian Journal of Surgery, 2022)
Objective: To find changes in voice quality, airway invasion during swallowing, pharyngeal residue after swallowing, acoustic and aerodynamic measurements and pulmonary function tests after total parathyroidectomy plus auto-transplantation for secondary hyperparathyroidism. Methods: We recruited 38 patients who underwent successful surgery for secondary hyperparathyroidism in this study. Voice quality was evaluated using voice handicap index (VHI-10), eating assessment tool (EAT-10), voice impairment, and the grade, roughness, breathiness, asthenia, strain (GRBAS) scale. Acoustic and aerodynamic measurements included fundamental frequency (F0), maximal phonation time, high pitch, jitter, s/z, shimmer and noise-to-harmonic ratio. Vocal cord mobility, vocal cord closure, premature spillage, the penetration–aspiration scale and the Yale pharyngeal residue severity rating scale (PRSRS) after swallowing were examined using fiber-optic endoscopy. Pulmonary function tests included forced vital capacity, forced expiratory volume in 1 s, bronchodilator test, total lung capacity, diffusion capacity of the lung for carbon monoxide, alveolar volume, and distance and O2 desaturation of the 6 min walking test (6MWT). Results: Four months after successful parathyroidectomy, VHI-10 improved significantly (p < 0.01); incomplete vocal cord closure decreased significantly (p < 0.01); the Yale PRSRS for vallecula and pyriform sinus improved significantly (p = 0.02 and p = 0.02); F0 and high pitch increased significantly (p < 0.01 and p = 0.01); O2 desaturation (<4%) of 6MWT improved significantly (p = 0.04). Conclusions: Parathyroidectomy for secondary hyperparathyroidism can improve the voice quality, vocal cord closure, the Yale PRSRS for vallecular and pyriform sinus and O2 desaturation of 6MWT, and increase F0 and high pitch.